Effect of Menstrual Restriction on Health, Education, and Empowerment of Women: A Review of Literature - Paudel, Radha; Budhathoki, Chitra Bahadur; Shahi, Prakash (Europasian Journal of Medical Sciences, 2021)
A menstrual restriction is a form of social suffering which is also identified as a violation of the constitutional right globally. But menstrual restriction-related work is still a neglected area. This paper has adopted traditional types of reviews to conceptualize how the health, education, and empowerment of women have been affected by the menstrual restriction. This study suggests, the menstrual-related restriction is not only a developing world issue but exists globally and has a high impact on a girl’s health, education, and empowerment. Though, theresearch on implementation and evaluation of the menstrual restriction is still needed to establish the evidence.